The knowledge, attitude and practices of male sports participants to sports-related dental trauma in Khobar and Dammam, Saudi Arabia - A pilot survey - Ibrahim Al-Arfaj; Ahmad Al-Shammari; Turki Al-Subai; Ghanim Al-Absi; Mohammad AlJaffari; Ahmad Al-Kadi; Maha El Tantawi; Asim Al-Ansari (Elsevier, 2016)
The risk of dental trauma may increase during sports participation. The purpose of this study was to evaluate the knowledge, attitude, and practices of sports participants concerning sports-related dental trauma and associated emergency/preventive practices. The study included 124 male subjects over 18 years of age participating in contact and non-contact sports in three clubs in the Eastern Province, Saudi Arabia. A questionnaire was used to assess past experience of dental trauma related to sports in addition to the use of a mouth guard and knowledge of related emergency procedures. Outcomes were compared between individuals practicing direct and non-direct contact sports. One third of the participants had experienced dental trauma while playing sports, mostly crown fracture, mobility, and avulsion. Their knowledge of first aid and emergency procedures was inadequate. A significantly higher proportion of non-direct contact sport participants sought the help of a dentist for themselves or others (P = 0.04 and 0.003, respectively). Only 33.9% used mouth guards, with higher odds of mouth guard use associated with participating in direct contact sports and believing a tooth can be lost during sports practice (odds ratio = 5.59 and 5.37, respectively). Educational programs are needed to increase the awareness in sports participants of the risk of dental trauma during sports participation, to improve their knowledge of first aid procedures, and to increase the use of mouth guards. Keywords: Sports, Dental trauma, Mouthguards